Serum metabolic variables associated with impaired glucose tolerance induced by high-fat-high-cholesterol diet in Macaca mulatta - Li, X.; Chen, Younan; Liu, J.; Yang, G.; Zhao, J.; Liao, G.; Shi, M.; Yuan, Y.; He, S.; Lu, Y.; Cheng, J. (2012)
Dyslipidemia caused by 'Western-diet pattern' is a strong risk factor for the onset of diabetes. This study aimed to disclose the relationship between the serum metabolite changes induced by habitual intake of high-fat and high-cholesterol (HFHC) diet and the development of impaired glucose tolerance (IGT) and insulin resistance through animal models of Macaca mulatta. Sixteen M. mulatta (six months old) were fed a control diet or a HFHC diet for 18 months. The diet effect on serum metabolic profiles was investigated by longitudinal research. Islet function was assessed by intravenous glucose tolerance and hyperinsulinemic - euglycemic clamp test. Metabonomics were determined by 1H proton nuclear magnetic resonance spectroscopy. Prolonged diet-dependent hyperlipidemia facilitated visceral fat accumulation in liver and skeletal muscle and disorder of glucose homeostasis in juvenile monkeys. Glucose disappearance rate (KGlu) and insulin response to the glucose challenge effects in HFHC monkeys were significantly lower than in control monkeys. Otherwise, serum trimethylamine-N-oxide (TMAO), lactate and leucine/isoleucine were significantly higher in HFHC monkeys. Sphingomyelin and choline were the most positively correlated with KGlu (R2 = 0.778), as well as negative correlation (R2 = 0.64) with total cholesterol. The HFHC diet induced visceral fat, abnormal lipid metabolism and IGT prior to weight gain and body fat content increase in juvenile monkeys. We suggest that increased serum metabolites, such as TMAO, lactate, branched-chain amino acids and decreased sphingomyelin and choline, may serve as possible predictors for the evaluation of IGT and insulin resistance risks in the prediabetic state. © 2008 Society for Experimental Biology and Medicine.